Barium Abundances of Common Stars in the Gaia-ESO Survey and the LAMOST Medium-resolution Survey - Tian-Yi Chen; Jian-Rong Shi; Hong-Liang Yan; Shuai Liu; Chun-Qian Li; Xiao-Jin Xie; Ze-Ming Zhou; Yao-Jia Tang; Ming-Yi Ding (The Astrophysical Journal)
Barium (Ba) abundance has been used as a crucial tracer of both slow and rapid neutron-capture processes to constrain the evolutionary models of the Galaxy. In this study, we aim to establish a reference sample with high-resolution spectra and high-quality stellar parameters from the Gaia-ESO Survey (GES). This sample explores the non–local thermodynamic equilibrium (NLTE) effects on the Ba abundances and will support future measurements of Ba abundances for the Large Sky Area Multi-Object Fiber Spectroscopic Telescope (LAMOST) medium-resolution survey (MRS). The sample is composed of 85 common stars of LAMOST MRS DR9 and GES DR5.1, complemented by four metal-poor ([Fe/H] < −1 dex) stars from AMBRE-UVES. The stars cover the ranges of stellar parameters as 4152 K ≤ T _eff ≤ 6866 K, 1.37 $\leqslant \,{\rm{log}}\,g\,\leqslant \,$ 4.57, and −2.40 dex ≤ [Fe/H] ≤ +0.25 dex. We derive the Ba abundances from three Ba ii absorption lines at λλ 5853, 6141, and 6496 Å of R = 47,000 UVES spectra through the spectral synthesis method using the local thermodynamic equilibrium (LTE) and NLTE assumptions. Compared to the GES catalog, the LTE Ba abundances obtained by us from the Ba ii λ 5853 line are the closest to the GES LTE results. The NLTE hypothesis is found to show various impacts on the three lines. The maximum differences from LTE abundances are 0.2, 0.5, and 0.6 dex for the Ba ii lines at λλ 5853, 6141, and 6496 Å, respectively. The NLTE corrections present opposite signs around [Fe/H] = −2.0 dex for the Ba ii line at λ 5853. Stars with higher temperatures or higher Ba abundances suffer larger NLTE effects. A more consistent result of the three lines confirms the necessity of taking NLTE effects into account when determining the Ba abundances.